Child's play : how can tactile textiles be used to assist social-emotional wellbeing in new entrants classrooms in primary schools? : an essay presented in partial fulfilment for the degree of Master of Design, Massey University, Wellington, New Zealand - Lee, Georgia (Massey University, 2021)
This project looks at the transitional period from early childhood education to primary school and how to ease the stress and anxiety from moving into a new environment. Such big changes at this developmental point have a great impact on a child's social-emotional wellbeing, and the stress in this transition can affect their ability to regulate themselves emotionally or interact socially. This transition to school could be significantly eased by adjusting the environment to the child instead of the child adjusting to the environment, using textiles to create interactive wall coverings that adjust the environment of a primary school classroom. Built on research into social-emotional wellbeing and learning through play, these tactile textile concepts aim to create positive play interaction in line with play-based learning initiatives supported by early childhood education. Processes such as print through interactive inks, knitting, sculpture, foiling and flocking have been explored to create highly tactile textile concepts. The design outcomes use tactility and the sense of touch to create a sense of playfulness in the classroom that mimics play-based learning. On a wider scale, these interactive textile concepts support social-emotional wellbeing through creating an environment that allows a child to feel as excited for school as the moment they turned five.
Keywords: 330310 Interaction and experience design